PENGARUH KEPEMIMPINAN, KOMPENSASI, BUDAYA ORGANISASI, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL - Moh. Sutoro; Syamsi Mawardi; Endang Sugiarti (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
Bureaucratic reform demands changes in clean governance, one of which is by improving the quality of human resources. The realization of good governance is the implementation of good public services. Thus, performance demands are inevitable. This research was conducted to examine the factors that influence the performance of employees in government circles, and to prove this research, a quantitative approach with multiple regression analysis was used. The sample technique uses simple random sampling with a number of respondents 118, and the unit of analysis is an employee of the ministry of youth and sports. The results showed that in government circles, the role of leadership is very influential. This happens because of the structural or bureaucratic work system, placing the leadership as the person in full control of all employees. So it is not surprising, if the leadership's order is often perceived as an organizational order, absolutely.